THE SMALL - MEDIUM INDUSTRY AND SELF-FULFILLMENT GONTOR DARUL MA’RIFAT STUDENTS ISLAMIC BOARDING SCHOOL IN KEDIRI - REZA FAHMI; PRIMA ASWIRNA; ASNAWIR ASNAWIR (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". The research based on the fact that the Gontor Darul Ma'rifat Modern Islamic Boarding School of Modern Islamic Boarding School has been operated the many kind of samll and medium industry. The students Involved in many kind of small and medium industry the which they held. They want to build through the buisness Reviews their selffulfiment that they hold. The aim of the study; (1) to describe the small and medium industry Darul Ma'rifat roomates Modern Islamic Boarding School of Islamic Boarding School Operate. (2) to describe about the character of students who manage the small and medium industry. (3) Correlation between management character and self-fulfillment of students. Then, one hundrad and seventy two students were a population the the study. The sample size count by Slovin formula (n = N / 1 + N.e2). So, the sample of students were only about one hundrad and twenty students. The Data collected by psychological scale, interviews and documentation of data. The Data Analyzed with statistical package of social science (SPSS) Version of 24. The result: (1) There were therty one kind of small and medium industry held by Darul Ma'rifat roomates Modern Islamic Boarding School of Islamic Boarding School. (2) There were three kionds character of students (honesty, decipline and responsible) who manage the small and medium industry. (3) There were correlation between small-medium industry and self-fulfillment students. 3. According To Pearson correlation the research got the coefficient correlation r count> r table (0.275> 0.211). It means rijected H0 and Ha has been recieved. So, there were correlation between small-medium industry and self-fulfillment students.